2018
DOI: 10.1016/j.compositesb.2018.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Development of a closed-loop recycling process for discontinuous carbon fibre polypropylene composites

Abstract: In this study the effects of a closed-loop recycling methodology are evaluated for degradation using a discontinuous carbon fibre polypropylene (CFPP) composite material. The process comprises two fundamental steps, reclamation and remanufacture. The material properties are analysed over two recycling loops. For neat polypropylene, the molecular weight analysis indicates evidence of minimal matrix degradation that does not affect the material behaviour, as demonstrated by the shear tests. CFPP specimens show n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 30 publications
0
54
0
1
Order By: Relevance
“…The use of fibres significantly beyond the critical length has in large part made up for deficiencies of the interface through the simple addition of interface area. In concurrent work, closed-loop recycling of thermoplastic matrix composites was investigated which showed an increase in strength over multiple recycling loops which shows an increase in strength may be possible by optimizing the fibre-matrix interface [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of fibres significantly beyond the critical length has in large part made up for deficiencies of the interface through the simple addition of interface area. In concurrent work, closed-loop recycling of thermoplastic matrix composites was investigated which showed an increase in strength over multiple recycling loops which shows an increase in strength may be possible by optimizing the fibre-matrix interface [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was chosen to use 3 mm carbon fibres to ensure the critical length was exceeded. Toho Tenax C124 fibres were used which have been used with the HiPerDiF fibre alignment method before [ 15 , 17 , 63 , 64 ]. These fibres have a water-soluble sizing which allows them to disperse well in water which aids the HiPerDiF fibre alignment process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This new method fabricates highly aligned discontinuous preforms directly from discontinuous fibers by suspending the discontinuous fibers in water and spraying the fiber suspension between several parallel plates. This technique is suited for production of polymer composites from recycled fibers [9][10][11][12], and is also applicable for mixing different fiber types [13] as well as fiber lengths [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, although the environmental conditions influence, mainly oxidation in the case of PP‐based composites, on the mechanical and physical properties have been investigated for many years and well understood , few studies were realized on the thermal aging influence on the local damage mechanisms of CFs‐reinforced polymer. Some of previous papers dealing with oxidation effect on in situ damage investigation have shown that the generation of micro‐cracks creates paths for oxygen to penetrate through the fiber–matrix interface. Thus the interface is oxidized and the material lifetime is consequently reduced.…”
Section: Introductionmentioning
confidence: 99%